The ‘Intellected Thing’ (res intellecta) in Hervaeus Natalis - Taieb, Hamid (Vivarium, 2015)
This paper analyses the ontological status of the ‘intellected thing’ (res intellecta) in Hervaeus Natalis. For Hervaeus an intellected thing is not a thing in the outer world, but something radically different, namely an internal, mind-dependent entity, something having a peculiar mode of being, ‘esse obiective’. While Hervaeus often says that the act of intellection is directed upon real things, this does not mean that the act is directed upon things existing actually outside the mind. Hervaeus argues that the act of intellection is directed upon things existing ‘aptitudinally’ outside the mind, not actually outside the mind. A thing existing aptitudinally outside the mind is a mind-dependent entity, something having esse obiective. In order to establish this point, I will explain how the property ‘being intellected’ (esse intellectum) should be interpreted in Hervaeus’ philosophy. This property is a peculiar type of relation, namely a relation of reason that gives a peculiar ontological status to its bearer. To neglect the distinction between actually outside and aptitudinally outside could falsely lead one to ascribe to Hervaeus a theory of intellection where the mental act is directed upon mind-independent entities.